IMPLEMENTASI RFID UNTUK MENINGKATKAN EFISIENSI LAYANAN SIRKULASI DI PERPUSTAKAAN - Akhmad Fadhel Baroqah (Jurnal Riset Sistem Informasi, 2025)
This study examines the implementation of Radio Frequency Identification (RFID) technology in enhancing the efficiency of library circulation services. RFID technology offers an innovative solution for managing collections and circulation services, such as borrowing and returning books, which were previously done manually. Utilizing radio waves, RFID enables automatic identification, tracking, and security of collections, thereby improving data accuracy and operational efficiency. This study employs a literature review approach to evaluate the benefits, challenges, and optimization strategies of RFID adoption in libraries. The findings indicate that RFID can reduce service time, enhance user experience, and support self-service features such as self-check and book-drop systems. However, challenges such as high implementation costs and the need for librarian training remain significant barriers. This study aims to provide guidance for libraries looking to adopt RFID technology to improve their services and maintain relevance in the digital era.